Inventarisasi Dan Identifikasi Jenis Tumbuhan Famili Asteraceae Di Kawasan Jawa Barat - Amandari, Nurul Fuji; Fadillah, Rafika Nur; Supriyatna, Ateng (Universitas Gajah Putih, 2023)
The introduction of the Asteraceae family is actually known for its many types. There is a family of Asteraceae which has spread widely to reach 125 to 300 genera and has around 20,000 to 25,000 species that have spread all over the world. This research was conducted in May-June 2023. The purpose of conducting this research was to determine the inventory and identification of plant species in the Asteraceae family in the Province of West Java. As well as to determine the morphology, characteristics, and habitus of the Asteraceae family in the Province of West Java. The method used in this study was a direct survey, and a review of literature studies to obtain other data sources. Based on the results of the research conducted, there are seven plant species in the Asteraceae family in the Province of West Java. The seven species are Asterai, Tithonia diversifolia, Sphagneticola trilobata, Chrysanthemum indicum, Chrysanthemum grandiflorum, Chrysanthemum himbeerrot, Chrysanthemum. These existing species describe distinct morphologies. Each type of plant has different benefits. The conclusion obtained from this study is that the Asteraceae family has many existing species, so it is expected to be able to find various species that are also able to conduct an inventory and identify plant species of the Asteraceae family in the West Java Province area in an objective and relevant manner.